DAMPAK RISIKO PAJAK DAN GOOD CORPORATE GOVERNANCE TERHADAP BIAYA MODAL PADA PERUSAHAAN MANUFAKTUR - Hasanah, Lulu Atul; Puspitasari, Elen (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research aims to examine and analyze the impact of tax risk and good corporate governance (size of the board of directors, family ownership, managerial ownership, institutional ownership, audit committee, audit quality and independent commissioners) on capital cost on manufacturing companies listed on the Indonesia Stock Exchange for period 2018-2020. There are 62 samples of companies obtained from purposive sampling technique with 186 observational data. The results of the multiple linear regression analysis method prove that tax risk, size of the board of directors, family ownership, audit committee and audit quality have an impact on the cost of capital. Meanwhile, managerial ownership, institutional ownership and independent commissioners have no impact on the cost of capital in manufacturing companies listed on the IDX for the period 2018-2020.